2023
DOI: 10.3390/e25010113
|View full text |Cite
|
Sign up to set email alerts
|

A Spectrum-Saving Transmission Method in Multi-Antenna Satellite Communication Star Networks: Sharing the Frequency with Terminals

Abstract: Satellite communication networks have gradually been recognized as an effective way to enhance the ground-based wireless communication. Considering the weight restriction of payloads, multi-antenna technologies have recently come into use on satellite platforms, and are capable of generating beams flexibly to provide services. To avoid incurring interferences, adjacent beams are designed to take different spectral resources. Unfortunately, this may limit the simultaneously accessed terminals since the spectrum… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 28 publications
0
1
0
Order By: Relevance
“…Further, Ref. [16] extended the idea to multi-user cases. The results showed that the co-carried method can provide a promising ergodic sum rate with marginal bit error rate (BER) degradation.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Further, Ref. [16] extended the idea to multi-user cases. The results showed that the co-carried method can provide a promising ergodic sum rate with marginal bit error rate (BER) degradation.…”
Section: Literature Reviewmentioning
confidence: 99%